Lactic fermentation of cooked navy beans by Lactobacillus paracasei CBA L74 aimed at a potential production of functional legume‐based foods. (9th July 2020) - Colucci Cante, Rosa; Gallo, Marianna; Nigro, Federica; Passannanti, Francesca; Salameh, Dana; Budelli, Andrea; Nigro, Roberto
Abstract: In recent years, scientific interest in the development of non‐dairy‐based functional foods is increasing progressively and the fermentation of cereals, legumes, fruits and vegetable‐based foods is becoming an important scientific research topic for the production of new probiotic products. In particular, legumes represent a possible alternative to protein foods from animal origins and an adequate fermentation substrate as they contain high amount of nutrients, such as proteins, carbohydrates, fibres, vitamins, and minerals, which are all useful to the growth and metabolic activity of certain microorganisms. This work focuses on the feasibility of developing a dry legume‐based functional product using a fermentation process carried out on a 10% w/v navy bean suspension, in a lab‐scale stirred batch reactor. After soaking and cooking dried navy beans, the fermentation tests performed on the resulting medium using Lactobacillus paracasei CBA L74 showed a maximum bacterial count of 10 9  CFU/mL after 20 hours and a maximum lactic acid concentration of 1.9 g/L after 16 hours of process time. A freeze‐drying process was performed on the fermented bean suspension, showing a 2‐log microbial reduction and a bacterial viability in the resulting probiotic powder of 3.7 × 10 8  CFU/g.